Incidence, bacteriological profile and risk factor analysis of neonatal sepsis in a peri urban set up of North India - Upadhyay, Shalini; Chakravarti, Anita; Bharara, Tanisha; Agarwal, Priti (International Journal of Contemporary Pediatrics, 2020)
Background: The high incidence and antimicrobial resistance among the pathogens causing neonatal sepsis is alarming. In addition to substantial immediate mortality, survivors of infections in the neonatal period are at increased risk of long-term disability. The present study was conducted to know the bacteriological profile and risk factors associated with culture proven neonatal sepsis in a peri urban population. Methods: This study was conducted over a period of 4 year (2015-2019). On clinical suspicion, blood culture specimens were sent to microbiology laboratory. The organisms isolated from blood cultures were identified and tested for antimicrobial susceptibility. As part of infection control practices, environmental samples from the neonatal intensive care units were tested. Results: Of 907 blood cultures of neonates received in the microbiology laboratory, 20.7% were culture positive. Majority of the episodes occurred at or before 72 hours of life (81.4%). 54.3% were Gram positive cocci including Coagulase negative Staphylococci, Staphylococcus aureus and Enterococcus spp. The common Gram-negative pathogens included Escherichia coli, Klebsiella spp. and Pseudomonas spp. Common risk factors involved were preterm birth, low birth weight, premature rupture of membrane, prolonged labour and iatrogenic causes. Conclusions: The early signs of sepsis are often subtle and nonspecific. Therefore, a high index of suspicion is needed for early diagnosis. Rapid, reliable detection and appropriate case management can save lives of many new-borns.